Two nematodes, Dentinema trichomycteri n. g., n. sp. (Cosmocercidae) and Procamallanus chimusensis Freitas & Ibáñez, 1968 (Camallanidae), from catfishes Trichomycterus spp. (Pisces) in Colombia - Moravec, Frantisek; Chara, Julian; Shinn, Andrew P (Systematic parasitology, 2004)
Light and scanning electron microscopical examinations of nematode samples collected from the stomachs and intestines of catfishes Trichomycterus spp. (Trichomycteridae, Siluriformes) from three streams in Colombia revealed the presence of two species, Dentinema trichomycteri n. g., n. sp. (Cosmocercidae) (type-host Trichomycterus sp.) and Procamallanus ( Spirocamallanus ) chimusensis Freitas & Ibáñez, 1968 (Camallanidae). The new, monotypic genus Dentinema is characterised mainly by the presence of a triangular mouth surrounded by three poorly developed lips, four submedian cephalic papillae, three conical teeth in the well-developed buccal cavity, an elongate oesophageal isthmus which is clearly separated from the corpus, precloacal oblique muscle bands, and by the absence of a ventral sucker. P. chimusensis , recorded from Colombia for the first time, is redescribed from specimens collected from Trichomycterus chapmani (Eigenmann) (a new host record) and Trichomycterus sp.; new observations show that this species belongs to a small group of Procamallanus spp. exhibiting a distinct sexual diversity in the structure of the buccal capsule. P. pexatus Pinto, Fábio, Noronha & Rolas, 1976 is synonymised with P. chimusensis .
Keywords: Kolumbie; Female; Nematoda; Catfishes; hlístice; Animals; Microscopy, Electron, Scanning; ženské pohlaví; sumci; mužské pohlaví; Colombia; Male; zvířata; mikroskopie elektronová rastrovací